On some applications of a new integral transform. - Eltayeb, Hassan; Kilicman, Adem (Hikari Ltd, 2010)
In this work a new integral transform, namely Sumudu transform was applied to solve linear ordinary differential equation with and without constant coefficients having convolution terms. In particular we apply Sumudu transform technique to solve Spring-Mass systems, Population Growth and financial problem.